Local Wisdom Values of Rumoh Aceh - Maria Ulfahmi, Cut Gesti; Rohidi, Tjetjep Rohendi; Triyanto, Triyanto (Universitas Negeri Semarang, 2018)
The purpose of this article is to reveal the local wisdom values of Rumoh Aceh architecture in Garot Cut village. Local wisdom means the wisdom to face something. Aceh’s local wisdom is a reflection of Aceh’s cultural tradition that is manifested in Aceh’s traditional architecture, in this case is Rumoh Aceh in Garot Cut village. The formulation of problems in this research is local wisdom values that is expressed through Rumoh Aceh. This research aims at analyzing the local wisdom values in Rumoh Aceh. The method used in this research is qualitative with ethnographical approach. Data collecting techniques are observation, interview, and document study with primary and secondary data sources. The technique of data validity is through source triangulation and data analysis technique through the stage of data reduction, data presentation, and verification. The research is situated in Garot Cut village. Indrajaya district Pidie regency. The research findings show that Rumoh Aceh has local wisdom values. Those values are in the components of building shape and the traditional ceremony of Rumoh Aceh, the values are religious, moral, social, traditional, and sensitive on nature. The knowledge, attitude, and local wisdom behavior Rumoh Aceh teach the society to adapt, to care with cultural inheritance, and to form the system of social familial system.